2012
DOI: 10.1073/pnas.1121549109
|View full text |Cite
|
Sign up to set email alerts
|

Induced fit on heme binding to the Pseudomonas aeruginosa cytoplasmic protein (PhuS) drives interaction with heme oxygenase (HemO)

Abstract: Iron, an essential nutrient with limited bioavailability, requires specialized cellular mechanisms for uptake. Although iron uptake into the cytoplasm in the form of heme has been well characterized in many bacteria, the subsequent trafficking is poorly understood. The cytoplasmic heme-binding proteins belong to a structurally related family thought to have evolved as “induced fit” ligand-binding macromolecules. One member, Pseudomonas aeruginosa cytoplasmic protein (PhuS), has previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
42
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 27 publications
4
42
0
Order By: Relevance
“…2 A, Upper and B, Upper). These data are consistent with previous solution studies showing that heme binding shifts the sedimentation coefficient distribution for holo-PhuS and further protects the C-terminal domain from proteolysis (10). Interestingly, the HDX-MS data are not consistent with the recent apo-PhuS crystal structures, where the overall structural fold is almost identical to that of holo-PhuS, suggesting that the apoPhuS crystal structures are more representative of the ligandbound state (12,13).…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…2 A, Upper and B, Upper). These data are consistent with previous solution studies showing that heme binding shifts the sedimentation coefficient distribution for holo-PhuS and further protects the C-terminal domain from proteolysis (10). Interestingly, the HDX-MS data are not consistent with the recent apo-PhuS crystal structures, where the overall structural fold is almost identical to that of holo-PhuS, suggesting that the apoPhuS crystal structures are more representative of the ligandbound state (12,13).…”
Section: Resultssupporting
confidence: 79%
“…Previous studies from our laboratory have shown the interaction of PhuS with HemO is driven by a conformational change on ligand binding (6,10). Furthermore, the previously reported kinetics of heme transfer from PhuS to HemO are slow: on the second timescale at 34°C (11).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Once internalized heme is sequestered by the cytoplasmic heme-binding protein PhuS. In a series of in vitro studies we have shown that the cytoplasmic heme-binding protein PhuS forms a specific protein complex with the ironregulated heme oxygenase, HemO (7)(8)(9). Heme is transferred to HemO for further degradation with the release of iron, CO, and biliverdin IX (BVIX) ␦-and ␤-isomers (10,11).…”
mentioning
confidence: 99%
“…Several cytoplasmic hemebinding proteins share sequence homology with ChuS including HemS from Yersinia enterocolitica (Schneider and Paoli 2005;Stojiljkovic and Hantke 1994), Bartonella henselae (Liu et al 2012a) and PhuS from P. aeruginosa (Lansky et al 2006). It has been established however, that PhuS main role is not heme degradation rather than it binds heme and delivers it to its partner HO, HemO for degradation (Lansky et al 2006;O'Neill et al 2012). PhuS was also shown to convert heme to verdoheme in vitro, and the possibility that it delivers verdoheme to HemO in vivo was raised (Lee et al 2014).…”
Section: Introductionmentioning
confidence: 96%